2005
DOI: 10.1016/j.bmcl.2005.02.066
|View full text |Cite
|
Sign up to set email alerts
|

The development of new isoxazolone based inhibitors of tumor necrosis factor-alpha (TNF-α) production

Abstract: 4-Aryl-3-pyridyl and 4-aryl-3-pyrimidinyl based tumor necrosis factor-alpha (TNF-alpha) inhibitors, which contain a novel isoxazolone five-membered heterocyclic core are described. Many showed sub-micromolar activity against lipopolysaccharide-induced TNF-alpha production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Many isoxazole-containing heterocycles have diverse biological activity, including antimicrobial, fungicidal, anticonvulsant, HDAC inhibitory, protein-tyrosine phosphatase 1B (PTP1B) inhibitory, analgesic, antioxidant, anti-apoptotic, anti-obesity, COX-2 inhibitory, nematicidal, anti-nociceptive, anti-inflammatory, antiviral, anti-tubercular, herbicidal, protein kinase C (PKC) inhibitory, and antineoplastic [101][102][103][104][105][106][107] activity. The isoxazole nucleus is also found in inhibitory agents [108], sulfisoxazoles [109], antibiotics [110,111], and anti-androgens [112,113]. Isoxazoles are, thus, very attractive synthetic targets for investigation of efficient and green synthetic methods.…”
Section: Introductionmentioning
confidence: 98%
“…Many isoxazole-containing heterocycles have diverse biological activity, including antimicrobial, fungicidal, anticonvulsant, HDAC inhibitory, protein-tyrosine phosphatase 1B (PTP1B) inhibitory, analgesic, antioxidant, anti-apoptotic, anti-obesity, COX-2 inhibitory, nematicidal, anti-nociceptive, anti-inflammatory, antiviral, anti-tubercular, herbicidal, protein kinase C (PKC) inhibitory, and antineoplastic [101][102][103][104][105][106][107] activity. The isoxazole nucleus is also found in inhibitory agents [108], sulfisoxazoles [109], antibiotics [110,111], and anti-androgens [112,113]. Isoxazoles are, thus, very attractive synthetic targets for investigation of efficient and green synthetic methods.…”
Section: Introductionmentioning
confidence: 98%
“…Ring oxygen of the coumarin nucleus, superimposing over the pyrimidine nitrogens in the leads, can interact with the main chain -NH-of Met-109 through Hbonding. Introduction of the -NO 2 group on phenyl ring was expected to increase activity based on the reported increase in activity by a strongly electron withdrawing substituents at that position [14]. However, compound 4 was found to be less potent than 3 which suggested that -NO 2 group at 4-position of phenyl ring may be responsible for decreased receptor ligand interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous heterocyclic systems bearing varied functional groups have been reported to inhibit TNF-Į production through inhibition *Corresponding author. E-mail: enein@gawab.com of p38 kinase [4][5][6][7][8][9][10][11][12][13][14]. More than 234 patents on small molecules claiming to be p38 kinase inhibitors have been published since 1996 and 17 specific inhibitors are selected for further development [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of new compounds for the treatment of tuberculosis is an important under taking in medicinal chemistry research. 1,3,4-Thiadiazole derivatives have received much attention due o their versatile biological activities as antibacterial (3)(4)(5), antitubercular (6-10), antifungal (11), antiviral (12,13), anticancer (3,(14)(15)(16)(17), antiproliferative (18), antiinflammatory, analgesic and antipyretic (19). Pyrazolinones have also shown various biological activities (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%